Pengaruh Kualitas Pelayanan, Kualitas Produk dan Persepsi Harga Terhadap Keputusan Pembelian di Beau Bakery Panglima Polim - Rohmawati Rohmawati; Salman Paludi (LPPM Universitas Asa Indonesia, 2023)
The more intense the business competition, the more companies are required to move more rapidly in terms of attracting consumers. This study examines the impact of service quality, product quality, and price perceptions on purchasing decisions at Beau Bakery Panglima Polim. sampling and sampling method using accidental sampling. The survey method for collecting data in the study was used with a structured questionnaire, for analysis of the hypothetical relationship in this research model namely multiple linear regression analysis as well as assistance software SPSS version 20. The survey starts this month December 2022 until January 2023 is located Outlets of Beau Bakery Panglima Polim by spreading a questionnaire to buyers at Beau Bakery Panglima Polim 100 respondents. The results show that quality Service, Product Quality, and Perceived Price simultaneously have a significant effect on purchasing decisions, and partially service quality and perceived price on purchasing decisions have a significant influence, except product quality on purchasing decisions has no significant effect